Effect of free range rearing on growth and meat quality of three different local chicken’s phenotypes - Azdinia Zidane; Adda Ababou; Mourad Taherti; Sarra Metlef; Leila Gadouche (Acta Scientiarum. Animal Sciences, 2023)
The present study was undertaken in order to evaluate the growth performances and meat quality of three indigenous chickens phenotypes reared under extensive conditions in the region of Chlef in Algeria. A week after hatching, 3 random groups of 35 chicks from each phenotype; normal plumage free-range chicken (NPFRC), crested free-range chicken (CFRC) and naked neck free-range chicken (NNFRC) were chosen and reared in free-range conditions for 18 weeks. The highest growth performance was shown by the crested free-range chicken (CFRC). In terms of meat quality, the analysis of variance (ANOVA) showed that crested phenotype (CFRC) showed the best nutritional qualities especially proteins and moisture. The discriminant analysis revealed that CFRC and NNFRC were better in terms of tenderness and overall acceptability. As consequence of these very interesting qualities, these local breeds should be considered for extensive production in order to provide a good quality meat, while assuring their preservation